2022
DOI: 10.3390/nano12122036
|View full text |Cite
|
Sign up to set email alerts
|

Nanosafety Analysis of Graphene-Based Polyester Resin Composites on a Life Cycle Perspective

Abstract: The use, production, and disposal of engineering nanomaterials (ENMs), including graphene-related materials (GRMs), raise concerns and questions about possible adverse effects on human health and the environment, considering the lack of harmonized toxicological data on ENMs and the ability of these materials to be released into the air, soil, or water during common industrial processes and/or accidental events. Within this context, the potential release of graphene particles, their agglomerates, and aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…449 Recent studies have shown that graphene-based polyester resin composites are released during machining and in weathered samples. 450 Cell viability levels of around 60% in A549 human lung cancer cells were observed with high dose (100 ppm) graphene nanosheets and graphene composites. Both graphene and resin demonstrated low toxicity although the authors acknowledged the presence of ambient particles from the spraying process that comprised of various metals.…”
Section: Life Cycle Perspective On 2d Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…449 Recent studies have shown that graphene-based polyester resin composites are released during machining and in weathered samples. 450 Cell viability levels of around 60% in A549 human lung cancer cells were observed with high dose (100 ppm) graphene nanosheets and graphene composites. Both graphene and resin demonstrated low toxicity although the authors acknowledged the presence of ambient particles from the spraying process that comprised of various metals.…”
Section: Life Cycle Perspective On 2d Materialsmentioning
confidence: 97%
“…It is also important when analyzing toxicity to consider that nanoparticles on surfaces, as opposed to compounded in a matrix, are not directly comparable . Recent studies have shown that graphene-based polyester resin composites are released during machining and in weathered samples . Cell viability levels of around 60% in A549 human lung cancer cells were observed with high dose (100 ppm) graphene nanosheets and graphene composites.…”
Section: Life Cycle Perspective On 2d Materialsmentioning
confidence: 99%